Music Listening and Communication Skills Improvement for Children up to Three Years - Kušnere, Sandija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
Theoretical part of paper will be devoted to an important problem at an early age the child’s development i.e. listening skills and communication skills development for children up to three years. The aim of the report – explored music listening and communication skills development opportunities for children up to three years. The theoretical part will be based on scientific research. The empirical part will be offered and described in music lessons, which will improve the communication skills of children up to three years. The paper will be used qualitative method research approach which will consist of a children’s activity monitoring, observation describe their interpretation of the results obtained and conclusions.Conclusions of the paper: in music lesson, it is possible to improve communication skills, using gestures, facial mimicry, body language, which is supplemented with is supplemented with voice intonation. Communication skills for children up to three years are non-verbal communication, whith includes facial mimicry, body language, gestures, different voice intonation and vocalization. Listening to music in music lessons should be used voice and body movements it easier to remember the musical material and can improve the communication skills of children up to three years.